2004
DOI: 10.1016/j.otohns.2003.09.018
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of 3599 Midfacial and 1141 Orbital Blowout Fractures Among 4426 United States Army Soldiers, 1980–20001

Abstract: We report the results from one of the largest series of midfacial and orbital floor blowout fractures from a population that crosses urban, rural, and foreign boundaries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
59
1
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(75 citation statements)
references
References 16 publications
(87 reference statements)
7
59
1
3
Order By: Relevance
“…We think that this difference occurred because of the socioeconomic and cultural differences of the local population studied. [1][2][3] In the epidemiological literature, it has been reported that the principal etiology of orbital fractures was traffic accidents, followed by, in decreasing order of frequency, physical assault, sports injuries and falls. [9,10] In their review, Cruz and Eichenberger [11] indicated that the most common cause of orbital fractures in urban areas is traffic accidents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We think that this difference occurred because of the socioeconomic and cultural differences of the local population studied. [1][2][3] In the epidemiological literature, it has been reported that the principal etiology of orbital fractures was traffic accidents, followed by, in decreasing order of frequency, physical assault, sports injuries and falls. [9,10] In their review, Cruz and Eichenberger [11] indicated that the most common cause of orbital fractures in urban areas is traffic accidents.…”
Section: Discussionmentioning
confidence: 99%
“…[9,10] In their review, Cruz and Eichenberger [11] indicated that the most common cause of orbital fractures in urban areas is traffic accidents. The study conducted by Shere et al [3] on American soldiers determined that assault was the most frequent etiology, followed by traffic accidents. The etiology of orbital fractures in our cases was traffic accidents, assaults and falls, in order of decreasing frequency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…O zamandan beri çeşitli çalışmalarda benzer toplumlardaki yüz kırıklarının görülme sıklığı ve epidemiyolojisi incelenmiştir 5,6 . Son yapılan çalışmalarda çocuklardaki 7,8 , ciddi travmalı hastalardaki 9 ve askeri topluluklardaki 10 yüz kırıkları değerlendirilmiştir.…”
Section: Discussionunclassified
“…4,31 Shere et al 31 found that 14.1% of blowout fractures were the result of sports in a military population. This was the third most common source in a study of 1141 blowout fractures in United States Army Soldiers over a 20-year period.…”
Section: Discussion Epidemiologymentioning
confidence: 99%